Residential Sector Energy Consumption at the Spotlight: From Data to Knowledge - Gouveia, João Pedro Costa Luz Baptista (2017)
Energy consumption is at the core of economic development, but its severe impacts on resources depletion and climate change have justified a call for its general reduction across all economic activities. Lowering households’ energy demand is a key factor to achieve carbon dioxide emission reductions as it has an important energy-saving potential. Households in the European Union (EU28) countries have a significant weight (25%) in the total final energy consumption. However, a wide range of variation is observed within the residential sector from 7.6 to 37.4 GJ per capita/annum, with the lowest consumption indicator observed in Southern EU countries. Energy consumption in the residential sector is a complex issue, explained by a combination of different factors. To pinpoint how to reduce energy consumption effectively while deliver energy services, we need to look not just at technology, but also to the factors that drive how and in what extent people consume energy, including the way they interact with technology (i.e., energy efficiency). The main objective of this research is to understand the differences in energy consumption arising from different socio-demographic, technologic, behavioral and economic characteristics of residential households. This research brings to the spotlight the needs and benefits of looking deeper into residential sector energy consumption in a southern European country. Portugal and the municipality of Évora, in particular, were selected as case studies. Residential sector consumption is a moving target, which increase the complexity of adequate policies and instruments that have to address the bottleneck between increase demand for e.g. climatization due to current lack of thermal comfort and to comply with objectives of increased energy efficiency which ultimately intend to reduce energy consumption. This calls for different levels of knowledge to feed multiscale policies. This dissertation expands the understanding of energy consumption patterns at households, consumers’ role in energy consumption profiles, indoor thermal comfort, and the levels of satisfaction from energy services demand. In a country potentially highly impacted by climate change, with low levels of income and significant lower energy consumption per capita compared to the EU28 average, looking into these issues gains even more importance. The work combines detailed analysis at different spatial (national, city and consumers level) and time scales (hour to annual) taking advantage of diverse methods and datasets including smart meters’ data, door to door surveys and energy simulation and optimization modelling. The results identify (i) ten distinct residential sector consumer groups (e.g., under fuel poverty); (ii) daily and annual consumption patterns (W, U and flat); (iii) major energy consumption determinants such as the physical characteristics of dwellings, particularly the year of construction and floor area; climatization equipment ownership and use, and occupants’ profiles (mainly number and monthly income). It is (iv) recognized that inhabitants try to actively control space heating, but without achieving indoor thermal comfort levels. The results also show (v) that technology can overweight the impact of practices and lifestyle changes for some end-uses as space heating and lighting. Nevertheless, important focus should be given to the evolution in the future of uncertain parameters related with consumer behavior, especially those on climatization, related to thermal comfort and equipment’s use. Furthermore, the research work presents a (vi) bottom-up methodology to project detailed energy end-uses demand, and (vii) an integrated framework for city energy planning. This work sets the ground for the definition of tailor-made policy recommendations for targeted consumer groups (e.g., vulnerable consumers) and climatization behavior/practices to reduce peak demand, social support policies, energy efficiency instruments and measures, renewable energy sources integration, and energy systems planning.